Evaluasi Program Corporate Social Responsibility Pt Medco E&P Indonesia: Studi Tingkat Kepuasan Masyarakat Terhadap Program Bibit Karet Organik Di Kecamatan Bts-Ulu Kabupaten Musi Rawas - Sutami Sutami; Alfitri Alfitri; Muhammad Yazid (Jurnal Empirika, 2018)
This research was conducted in six villages located in BTS-ULU Subdistrict, Musirawas Regency, South Sumatra Province. The research aims to measure the level of community satisfaction with organic rubber seedling (BUKOR) programs developed by PT Medco E & P Indonesia. The BUKOR program itself is actually a form of PT Medco E & P Indonesia's CSR (Corporate Social Responsibility) program. The research was conducted using a quantitative approach. The population of research was all community in BUKOR program participants in six villages namely Sungai Naek Village, Sungai Bonot Village, Pangkalan Tarum Village, Gunung Kembang Village, Lubuh Pauh Village, and Pelawe Village which were known amount of 159 people. Samples were taken as much as 50% of the total population and adjusted with the number of people from each village so that the number of samples was 81 people. Data collection techniques used are documentation and questionnaires. The results of the research revealed that the level of community satisfaction with the BUKOR program in the six research villages was included in the category of satisfied and very satisfied. The level of community satisfaction in the satisfied category is in Sungai Naek Village, Sungai Bonot Village, Pangkalan Tarum Village, Gunung Kembang Village. While the level of community satisfaction with very satisfied categories is in Lubuh Pauh Village and Pelawe Village.